Tensile-Property Characterization of Thermally Aged Cast Stainless Steels using Neural Networks - Nema, Atef (Basrah Journal for Engineering Sciences, 2010)
The effect of thermal aging on the tensile properties of cast stainless steel during service in light water reactors has been evaluated and recorded by the Argonne National Laboratory. Tensile data for several experimental and commercial heats of cast stainless steel (CF-8M) are presented for predicting the change in tensile flow and yield stresses and engineering stress-strain curve as a function of time and temperature of service in the light water reactors using Neural Networks. Thermal aging increases the tensile strength of this type of steel. The result and correlation described by this work may be used for assessing thermal embitterment of cast stainless steel components.